2021
DOI: 10.6061/clinics/2021/e2370
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss, tinnitus, and hypertension: analysis of the baseline data from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil)

Abstract: OBJECTIVES: To investigate the association among hypertension, tinnitus, and sensorineural hearing loss and evaluate the influence of other covariates on this association. METHODS: Baseline data (2008-2010) from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) were analyzed. Altogether, 900 participants were evaluated. The baseline assessment consisted of a 7-hour examination to obtain clinical and laboratory variables. Hearing was measured using pure-tone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
(62 reference statements)
3
7
0
Order By: Relevance
“…In this study, altogether, 25.40% of the workers included in our study had hypertension, suggesting a higher incidence of this disease. Workers particularly in the subgroups of male gender, aged > 35 years, exposure time with noise > 5 years, and smoking were more likely to develop hypertension, which in accordance with observed trends in previous studies (Evrard et al 2017;Li et al 2019;Samelli et al 2021;Talukder et al 2011). We concluded that workers with the above characteristics were high risk individuals of developing hypertension in occupational noise settings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, altogether, 25.40% of the workers included in our study had hypertension, suggesting a higher incidence of this disease. Workers particularly in the subgroups of male gender, aged > 35 years, exposure time with noise > 5 years, and smoking were more likely to develop hypertension, which in accordance with observed trends in previous studies (Evrard et al 2017;Li et al 2019;Samelli et al 2021;Talukder et al 2011). We concluded that workers with the above characteristics were high risk individuals of developing hypertension in occupational noise settings.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have found that 16% of worldwide hearing loss in adults caused by occupational noise (Nelson et al 2005). NIHL can cause communication disorder and result in social isolation, thus leading to self-abasement and cognitive decline and depression (Samelli et al 2021). Therefore, it is an extreme important public health goal to prevent NIHL and reduce its adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, altogether, 25.40% of the workers included in our study had hypertension, suggesting a higher incidence of this disease. Workers particularly in the subgroups of male gender, aged > 35 years, exposure time with noise > 5 years, noise exposure level > 85 dB (A) and smoking were more likely to develop hypertension, the results were in accordance with observed trends in previous studies [13,40,50,51]. Males were observed with much higher blood pressure levels and higher risk of hypertension compared with females.…”
Section: Discussionsupporting
confidence: 90%
“…Zhou J et al [12] has conducted a meta-analysis and found that the prevalence of occupational NIHL was 21.3% in China. NIHL could cause communication disorder and social isolation, thus leading to self-abasement, cognitive decline, and depression [13]. Therefore, it is an extreme important public health goal to prevent NIHL and reduce its adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, all these factors could cause a malfunction of the inner ear, resulting in HL and tinnitus [4]. In concordance with this fact, a study suggested that hypertensive patients were reported to have higher hearing thresholds as well as an increased prevalence of tinnitus [5]. Another study assessing the association between HL and HTN examined hearing by using frequencies between 250 and 8000 Hz to measure the pure tone threshold.…”
Section: Introductionmentioning
confidence: 95%